A Case of Small Bowel Obstruction and Enterocutaneous Fistulation Resulting from a Mesenteric Haematoma following Blunt Abdominal Trauma - Matthew North; Nicholas Aveyard; Oyeniyi Diya; Jeremy Berger; Maitham Al-Whouhayb (Case Reports in Surgery)
A 23-year-old male with a history of previous abdominal surgery was involved in a road traffic accident. He was discharged after initial assessment but represented several days with small bowel obstruction secondary to a mesenteric haematoma. He underwent resection and recovered well but represented later on the day of discharge with a leaking surgical wound consistent with an enterocutaneous fistula. This was managed conservatively and closed spontaneously after ten days. This case serves to highlight that adhesions from previous surgery can tether the small bowel causing mesenteric injury following blunt-force trauma. It also demonstrates that postoperative ileus can result in an enterocutaneous fistula that has the appearance of an anastomotic breakdown but which resolves more rapidly.